Aplikasi bay 'al-dayn dalam produk-produk pembiayaan perdagangan antarabangsa Islam - Abdul Rahim, Ahmad Khilmy; Mohamed Naim, Asmadi; Zainol, Zairani (Universiti Malaya, 2014)
International Trade Finance (ITF) instruments were introduced in Islamic banking system in Malaysia since the early 1990s when there is a need for Islamic instruments in commerce especially in international trade.Most of the financial products are based on conventional instruments such as Bank Guarantee (BG), Letter of Credit (LC), Accepted Bill (AB), Shipping Guarantee (SG), Export Credit Refinancing (ECR) and others.In order to be accepted in Islamic Finance, some amendments will have been made so that it will be ‘sharia compliant’ by applying muamalat contracts in those products.Muamalat contracts that are widely used in Islamic Trade Finance products are murabahah, bay‘ al-dayn, kafalah and wakalah.This article analyses the views of previous and contemporary Islamic scholars and experts in Islamic financial jurisprudence on the use of bay‘ al-dayn contracts.This article also analyses the application of Islamic Trade Finance products namely Accepted Bill (AB-i), Bill of Exchange Purchase (BEP-i) and Export Credit Refinancing (ECR-i).This study concludes that bay‘ al-dayn remains controversial in Islamic banking sector due to difference of opinions among the previous and current Islamic scholars.